Non-Curing Thermal Interface Materials with Graphene Fillers for Thermal Management of Concentrated Photovoltaic Solar Cells - Barath Kanna Mahadevan; Sahar Naghibi; Fariborz Kargar; Alexander A. Balandin (C, 2019)
Temperature rise in multi-junction solar cells reduces their efficiency and shortens their lifetime. We report the results of the feasibility study of passive thermal management of concentrated multi-junction solar cells with the non-curing graphene-enhanced thermal interface materials. Using an inexpensive, scalable technique, graphene and few-layer graphene fillers were incorporated in the non-curing mineral oil matrix, with the filler concentration of up to 40 wt% and applied as the thermal interface material between the solar cell and the heat sink. The performance parameters of the solar cells were tested using an industry-standard solar simulator with concentrated light illumination at 70× and 200× suns. It was found that the non-curing graphene-enhanced thermal interface material substantially reduces the temperature rise in the solar cell and improves its open-circuit voltage. The decrease in the maximum temperature rise enhances the solar cell performance compared to that with the commercial non-cured thermal interface material. The obtained results are important for the development of the thermal management technologies for the next generation of photovoltaic solar cells.